Pembelajaran dengan Cooperative Integrated Reading and Composition (CIRC) dalam Meningkatkan Kemampuan Menemukan Pokok Pikiran - Awatik, Awatik (Fakultas Bahasa dan Sains, Universitas Wijaya Kusuma Surabaya, 2019)
This study aims to improve students' abilities in finding points of thought. These efforts are carried out by applying the CIRC learning model. This research is a classroom action research conducted in class V-C SDN 004 / V Kuala Tungkal. The study was conducted in 2 cycles. There were 33 students who were the subjects in this study. The results showed a positive impact from the application of the CIRC model. This is indicated from the increase in the average student test score of 61.90 in the first cycle to 78.79 in the second cycle. In addition, the number of students who exceeded the minimum grade also increased, namely 51,52% (17 students) in the first cycle to 78,79 (26 students) in the second cycle. Keywords: CIRC, find the main idea.